Dragon Ball. Season two [videorecording (DVD)] - Toriyama, Akira, 1955- (FUNimation Entertainment, 2009)
After meeting his match in the World Martial Arts Tournament, Goku embarks on a mission to recover the Four Star Dragon Ball that once belonged to his grandfather. His treacherous quest will take him from the terrifying heights of Muscle Tower to the darkest depths of the deep blue sea. But, Commander Red, leader of the Red Ribbon Army is determined to seize the Dragon balls himself and then conquer the world. Includes booklet, trailers, and more.